Kinematic, kinetic and emg analysis of four front crawl flip turn techniques - Pereira S.M.* (2015)
© 2015 Taylor & Francis.This study aimed to analyse the kinematic, kinetic and electromyographic characteristics of four front crawl flip turn technique variants. The variants distinguished from each other by differences in body position (i.e. dorsal, lateral, ventral) during rolling, wall support, pushing and gliding phases. Seventeen highly trained swimmers (17.9 ± 3.2 years old) participated in interventional sessions and performed three trials of each variant, being monitored with a 3-D video system, a force platform and an electromyography (EMG) system. Studied variables: rolling time and distance, wall support time, push-off time, peak force and horizontal impulse at wall support and push-off, centre of mass horizontal velocity at the end of the push-off, gliding time, centre of mass depth, distance, average and final velocity during gliding, total turn time and electrical activity of Gastrocnemius Medialis, Tibialis Anterior, Biceps Femoris and Vastus Lateralis muscles. Depending on the variant, total turn time ranged from 2.37 ± 0.32 to 2.43 ± 0.33 s, push-off force from 1.86 ± 0.33 to 1.92 ± 0.26 BW and centre of mass velocity during gliding from 1.78 ± 0.21 to 1.94 ± 0.22 m s−1. The variants were not distinguishable in terms of kinematical, kinetic and EMG parameters during the rolling, wall support, pushing and gliding phases.